Kebijakan Perguruan Tinggi Negeri Yogyakarta Terhadap Penyandang Disabilitas - Akhmad Soleh (Jurnal Pendidikan Islam, 2014)
This study discusses the accessibility of university education in the four public universities in Yogyakarta; Indonesian Arts Institute (ISI), University of Gajah Mada (UGM), Yogyakarta State University (UNY), and State Islamic University (UIN) Sunan Kalijaga. Up to now, the disability groups have not got equal access and the opportunity in higher education. There are only a few students with disabilities that are accepted in Universities in Indonesia, because of physical limitations that would interfere with the teaching-learning process in their classrooms. The research findings showed that the education systems in the UGM, Yogyakarta State University, and the ISI have a system of “integration”, while at UIN has led to the inclusion system, which is “accommodative” and has the ability to service for persons with disabilities.